Analisis Faktor Kejadian Anemia Pada Petani Hortikultura - Norsita Agustina; Norfai Norfai (HB PRESS, 2018)
Anemia is a period of erythrocyte or circulating hemoglobin insufficient to its function to provide oxygen for body tissues. Laboratory, anemia is described as a decrease in hemoglobin levels and erythrocyte count and hematocrit below normal. The onset of anemia indicates bone marrow failure or excessive red blood cell loss.The purpose of this study is to find out and analyze the incidence of anemia in horticultural farmers. This research is an analytical survey with cross sectional approach. The population in this study amounted to 50 horticultural farmers in Banjarbaru Landasan Ulin Utara RT. 07 by taking samples using total sampling, which means the amount of sample is 50 respondents. Data on hemoglobin levels were obtained through laboratory tests in the basic laboratory of Banjarmasin Office and data on age, frequency of spraying and spraying duration were obtained by interview using questionnaires while completeness data on APD by observation. The results of data collection were analyzed using univariate, bivariate statistics with Che Square statistical tests using computer program aids with a 95% confidence level. Based on the results of the study, it was concluded that the variables that were not statistically significantly associated with the incidence of anemia in horticultural farmers were age, APD completeness, spraying frequency and spraying duration with p-value > (α) 0.05. Based on the results of these conclusions, it is recommended to conduct further research studies on the risk factors for the incident of anemia in horticultural farmers from the aspect of topographical factors of the place of study, rest factors and nutritional status.